Pengaruh Model Pembelajaran Discovery Learning Berbantuan Virtual Laboratory OLabs terhadap Hasil Belajar Siswa Kelas XI pada Materi Asam Basa - Khofivah Sri Qoriah; Ani Sutiani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the differences in learning outcomes, improvement in learning outcomes, and the effectiveness of the discovery learning model assisted by the Virtual Laboratory OLabs on acid-base material. The study used a quasi-experimental method with a pretest-posttest control group design. The study sample consisted of two classes of XI MAN 2 Model Medan, namely XI F1-A and XI F1-G. The experimental class applied the discovery learning model and the control class used the direct learning model. Both classes used the same media, namely the Virtual Laboratory OLabs, so that differences in learning outcomes were reviewed based on the applied learning model. Data were collected using a validated multiple-choice test. The results showed that the average post-test score of the experimental class (87.12) was higher than the control class (82.78). The improvement in learning outcomes in the experimental class was also better with an average N-Gain value of 0.74 (high category), while the control class obtained an N-Gain of 0.61 (medium category). The results of the hypothesis test showed a significance value of 0.001 (p < 0.05), indicating a significant difference in learning outcomes between the two groups. Thus, the discovery learning model assisted by the Virtual Laboratory OLabs is more effective than the direct learning model in improving student learning outcomes in acid-base material.